Cross sectional echocardiographic anatomy of common atrioventricular valve in atrial isomerism. Issue 4 (October 1989) - Arisawa, J; Morimoto, S; Ikezoe, J; Hamada, S; Kozuka, T; Sano, T; Ogawa, M; Matsuda, H; Kawashima, Y
Abstract : The morphology of the common atrioventricular valve and its relation to the ventricles was assessed by cross sectional echocardiography in 17 patients with atrial isomerism--four with left isomerism and 13 with right isomerism. In 13 patients the atrioventricular valve consisted of four leaflets: a large anterosuperior leaflet, two lateral leaflets, and a posteroinferior leaflet. The remaining four patients had two anterosuperior leaflets. Five patients had hearts with a double inlet right ventricle and all of them had a rudimentary left ventricle. All the commissures were attached to the right ventricle. Five patients showed severe right ventricular dominance. The atrioventricular morphology in these five hearts differed from that in the patients with the usual atrial arrangement, concordant atrioventricular connection, and hypoplasia of the left ventricle. Only the anterosuperior leaflet bridged the rudimentary left ventricle, and the posteroinferior leaflet was tethered to the ventricular septal crest. Six patients had a biventricular atrioventricular connection and two of them showed mild right ventricular dominance. The atrioventricular morphology in these hearts was the same as that seen in the patients with usual atrial arrangement and a concordant atrioventricular connection. The remaining patient showed dominance of the left ventricle. Only the anterosuperior leaflet bridged the rudimentary right ventricle in this heart.